The corporate culture survival guide - Schein, Edgar H (Jossey-Bass, 2009)
"A Warren Bennis book"; "Warren Bennis signature series"--P. [vi].; Includes bibliographical references and index; Why bother? -- What is culture anyway? -- What are the elements and dimensions of organizational culture? -- Deeper assumptions -- When and how to assess your culture -- Cultural learning, unlearning, and transformative change -- Culture creation, evolution, and change in start-up companies -- Culture dynamics in the mature company -- Mid-life crisis and potential decline -- When cultures meet: acquisitions, mergers, joint ventures, and other multicultural collaborations -- Cultural realities for the serious culture leader